The Long-Term Public Health Benefits of Breastfeeding - Binns, C.; Lee, M.; Low, Wah Yun (SAGE Publications, 2016)
Breastfeeding has many health benefits, both in the short term and the longer term, to infants and their mothers. There is an increasing number of studies that report on associations between breastfeeding and long-term protection against chronic disease. Recent research evidence is reviewed in this study, building on previous authoritative reviews. The recent World Health Organization reviews of the short- and long-term benefits of breastfeeding concluded that there was strong evidence for many public health benefits of breastfeeding. Cognitive development is improved by breastfeeding, and infants who are breastfed and mothers who breastfeed have lower rates of obesity. Other chronic diseases that are reduced by breastfeeding include diabetes (both type 1 and type 2), obesity, hypertension, cardiovascular disease, hyperlipidemia, and some types of cancer.